The Level of Utilization of Procurement Plan By Local Government Authorities in Ghana - Tei-Kpoti, William (2016)
A thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Science in Construction Management Programme